Pressure drop and flow distribution in parallel-channel configurations of fuel cells: U-type arrangement - Wang, Junye (International journal of hydrogen energy, 2008)
An analytical model based on mass and momentum conservation has been developed to solve the flow and pressure distribution in fuel cell stacks. While existing models neglected either friction effect or inertial effect, the present model takes both of them into account. The analytical solutions are fully explicit so that the velocity and pressure distribution in fuel cell stacks are directly correlated with the geometrical parameters of fuel cell stacks. Parameter Sensitivity is also analysed to determine the influence of geometrical structures and parameters on flow performance of fuel cell stacks. It is found that friction and momentum effects work in opposite directions, the former tending to produce a pressure drop and the latter a pressure rise. The proper balance of the two effects can result in less non-uniformity and an optimal design. Furthermore, the existing solution by Bassiouny and Martin [Flow distribution and pressure drop in plate heat exchanges. Part I. U-type arrangement. Chem Eng Sci 1984;39(4):693–700] is a special case of the present solutions without the friction effect and those by Kee et al. [A generalized model of the flow distribution in channel networks of planar fuel cells. J Power Sources 2002;109:148–59] and Maharudrayya et al. [Flow distribution and pressure drop in parallel-channel configurations of planar fuel cells. J Power Sources 2005;144:94–106] are another special case without inertial effect.